ALOE VERA IN SKIN BURNS: A NEW TREND OR AN EVIDENCE? - C. Pereira, Carina; Reis, Ana Rita; Pinho Cruz, Diana; Cardoso, Sarah (Journal of the Portuguese Society of Dermatology and Venereology, 2015)
Introduction: Since ancient times, aloe vera is a plant used for medicinal and cosmetic purposes, due to its various properties. Currently, in many countries, the treatment of burns is one of the main indications for its use. However, the clinical evidence is still unclear. Objective: Review the existing evidence concerning the effectiveness of aloe vera in the treatment of skin burns. Data sources: Medline, evidence based medical sites (National Guideline Clearinghouse Guideline Finder, Canadian Medical Association, The Cochrane Database, DARE and Bandolier), Portuguese Index of Medical Journal and references of selected articles. Methods Review: Bibliography search in these databases, using the following combination of MeSH terms: "burns" and "aloe", articles published up to June 2014, in Portuguese, English, French or Spanish. We used the Strength of Recommendation Taxonomy scale for the allocation of levels of evidence and recommendation strengths. Results: We found 236 articles and selected, as meeting the inclusion criteria, one systematic review with meta-analysis and 2 original articles. After analyzing the articles, generally it is verified a faster healing of burns using aloe vera, when compared to the control. Conclusion: The available evidence seems to support the effectiveness of aloe vera in the treatment of skin burns (SOR B). However, due to the heterogeneity of aloe vera formulations and control used in the various studies, it is not possible to draw a clear conclusion about this benefit. More studies with better quality are needed to prove the efficacy of aloe vera in the treatment of burns.